PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH - Taufik Rahman (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2019)
The ability analyzed in this study is the ability to think critically mathematically. This ability is considered very important as written is the goal of mathematics learning from the Ministry of National Education which states that the development of critical thinking skills is the focus of learning and becomes one of the graduation standards of high school students. It is desirable, high school graduates, have the ability to think logically, analytically, systematically, critically, and creatively, and have the ability to work together. This study aims to determine the improvement of mathematical critical mathematical thinking skills of students in one of the Vocational Schools in Bandung between those who obtain problem-based learning with those who obtain conventional learning. The sample in this study was one Vocational School in Bandung, which was selected by 2 classes, namely the first class obtained problem-based learning and the second class received conventional learning. The method in this study is a quasi experiment. The instrument in this study was a test instrument in the form of a description and consisted of 6 questions. The results of this study are improved mathematical critical thinking skills of students who get problem-based learning better than students who get conventional learning